EFEKTIVITAS MEDIA PEMBELAJARAN TEKA-TEKI SILANG (TTS) TERHADAP KEMAMPUAN MENGIDENTIFIKASI SIKLUS HIDUP MAKHLUK HIDUP SISWA KELAS IV SD NEGERI 101812 NAMO TUALANG TAHUN PEMBELAJARAN 2024-2025 - Br Barus, Zelya Margarena; Sutikno (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the Effectiveness of Crossword Puzzle Learning Media (TTS) on the Ability to Identify the Life Cycle of Living Things of Fourth Grade Students of SD Negeri 101812 Namo Tualang in the 2024-2025 Academic Year. This study is an experimental study that uses Crossword Puzzle learning media (TTS) and then finds out its effectiveness from the instruments that have been distributed to students. The population of this study were fourth grade students of SD Negeri 101812 Namo Tualang which consisted of two classes with a total of 60 people. From this number, a sample of 60 people was determined, namely the entire population became the sample. The sampling technique used the saturated Sampling technique, which means the entire population was sampled. The method used in this study is a post-test only design. The instruments used in this study were fill-in-the-blank questions for the control class and crossword puzzles (TTS) for the experimental class. From the results of the data analysis, it is known that the Crossword Puzzle learning media (TTS) is more effective in the ability to identify the life cycle of living things of fourth grade students of SD Negeri 101812 Namo Tualang. In this case, the average value obtained in the control class was 69.5, and the average value in the experimental class was 82.16. Based on the normality test, the results for the control class were normally distributed, with L count > L table (0.114 < 0.161), and the experimental class was also normally distributed, with L count > L table (0.126 < 0.161). Furthermore, the homogeneity test proved that the sample in this study came from a homogeneous population with F count < F table, namely 1.280 < 4.196. Furthermore, the hypothesis testing of this study was accepted with T count > T table, namely 5.01 > 2.04, proving that the Crossword Puzzle (TTS) learning media is effective in improving the ability to identify the life cycles of living things in fourth-grade students at SD Negeri 101812 Namo Tualang.